Ethical Leadership Behavior of Managers' and Nurses' Perceptions of Organizational Justice - Gözde Çitak; Burcu Bayrak Kahraman (Association of Nurse Managers, 2021)
INTRODUCTION: The study was carried out in order to determine the ethical leadership behaviors of managers and the perceptions of nurses related to organizational justice. METHODS: The universe of this descriptive research was composed of 177 nurses, who were working in a University Hospital. Data were collected through Sociodemographic question form, Ethical Leadership Scale and Organizational Justice Perception Scale. Data, frequency, percentage, arithmetic mean and standard deviation were evaluated with Mann- Whitney U test, Kruskal -Wallis-H test and Spearman correlation analysis. RESULTS: According to the results, the average scores of ethical leadership scale and Organizational Justice Perception Scale of the responsible nurses were significantly higher than the clinical nurses (p<0,05). There was a statistically significanty moderate and positive correlation between nurses' average scores of Organizational Justice Perception Scale and Ethical Leadership Scale (r=0,645, p<0,05) DISCUSSION AND CONCLUSION: In the study, it was concluded that the nurses found their managers ethical leadership behaviors at a medium level and that nurses' perceptions of organizational justice are at a moderate level.